Woody plants of the National Park Mavrovo, Republic of Macedonia - Simovski, Bojan (Bulgarian Academy of Sciences, Sofia, 2013)
The National Park Mavrovo situated in the North-Western part of the Republic of Macedonia range of three mountain massifs- Shar Planina, Korab and Bistra, with an area of about 73,000 ha. It is characterized by great floristic richness, in particular woody plants and forest communities. Part of this plant treasure has encountered in rare, endemic and Tertiary relic species. In the conducted field research mainly during the period 2009-2012 within the Park are determined 149 woody species, which is more than 45% of the Macedonian dendroflora. This represents the dendrofloral richness of the Park. In this paper originated from my MSc thesis are determined woody species as individuals, and within populations, i.e. as a part of the forest associations. Special significance is achieved with the discovery of some new finding sites of the species and dendrological phenomena. The results relate to ecological site characteristics of the dendroflora represented in the Park, and its bio-ecological specificity is expressed through a detailed data tables and charts.
Conference presentation
Keywords: woody plants; dendroflora; relic; endemic; National Park Mavrovo